Produção de celulases fúngicas por fermentação em estado sólido: ampliação de escala de biorreatores de leito fixo - Casciatori, Fernanda Perpétua [UNESP] (2015)
This thesis deal with the scale-up of packed-bed bioreactors for fungal cellulases production by solid-state fermentation (SSF), comprising experimental steps, developed in Brazil, and modeling and simulation, developed in Germany. At flasks scale, growth kinetic parameters were obtained for thermophilic fungus Myceliophthora thermophila I-1D3b and mesophilic one Trichoderma reesei QM9414. Growth was estimated based on protein content and specific growth rates were μ = 0,06 and 0,10 h-1 for thermo and mesophilic fungi, respectively. During the abroad period, it has been proposed a heterogeneous two-dimensional model able to predict temperature, moisture content and fungal growth profiles throughout the process at any position of the bioreactor. Simulations using this model for the cultivation of M. thermophila in a packed-bed bioreactor with internal diameter 7.62 cm addressed that is shouldn't happen overheating; however, moisture content profiles could harm enzyme productivity in the vicinity of the air inlet. On scaling-up, experiments in packed-bed bioreactors employing both fungi and sugar cane bagasse and wheat bran as substrates were carried out. The process yield was measured as cellulolytic activities, as well as temperature profiles along the process and final moisture contents of the fermented materials were obtained. For both fungi, in bioreactor with 7.62 cm diameter, there was no overheating of the bed when substrate contained bagasse fibers, agreeing with simulations. In bioreactor with 20 cm diameter, an expressive radial thermal profile has been observed, with temperature increasing up to 10 ºC at bed central axis. With thermophilic fungus M. thermophila, average activities of endoglucanase and xylanase reached, respectively, 785 and 2120 U/gss in thin-bioreactor and 580 and 2070 U/gss in large-bioreactor. With mesophilic fungus T. reesei, average activities of endoglucanase and ...